PERMAINAN TRADISIONAL BAKIAK UNTUK PENGEMBANGAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI KELURAHAN MARIANA - Elviana, Salwa; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the traditional Bakiak game for gross motoric development of children aged 5-6 years in kelurahan mariana kecamatan Pontianak kota. The method used is a qualitative method with descriptive approach. The data source of this research is children aged 5-6 years 6 people, 3 men, 3 women. Data collection tools through observation sheets, interview guidelines and documentation. Research result shows (1) this traditional Clog game has potential in develop aspects of child development including motor development namely strength, balance and agility. (2) the strength shown when the child is able to use his muscles to lift the Clogs then step one to the next, (3) the balance is shown in when a child walks using clogs by traveling the same distance determined without falling and walking in a straight line using sandals Clogs, (4) agility is shown when the child holds his feet to spin turn around without holding the Clogs and walk using the Clogs without holding his friend.